Improving the Quality of Elementary Teacher Education Learning through Student Activity-Oriented Learning Strategies - Verliyanti, Verliyanti (CV. Creative Tugu Pena, 2025)
This study aims to examine the application of student activity-oriented learning strategies in improving the quality of learning in the Elementary School Teacher Education (PGSD) program. The method used is classroom action research (CAR) which is implemented in two cycles, each consisting of planning, implementation, observation, and reflection. The subjects of the study were PGSD students who took courses related to learning strategies. Data collection instruments included observation, interviews, motivational questionnaires, learning outcome tests, and documentation. The results showed a significant increase in student engagement, learning outcomes, and motivation. In the first cycle, active student participation in group discussions reached 62%, projects 58%, and presentations 58%, with an average score of 72 and classical completion of 70%. In the second cycle, there was an increase to 85% in discussions, 88% in projects, and 82% in presentations, with an average score of 82 and classical completion of 90%. Student motivation also increased, as indicated by the proportion of highly motivated students, which rose from 45% in cycle I to 78% in cycle II. Interviews and documentation showed that learning became more enjoyable, interactive, and collaborative. These findings align with constructivist and sociocultural theories, which emphasize the importance of active engagement in learning, and support previous studies on the effectiveness of active learning. Therefore, a student-oriented learning strategy can be an effective approach to improving the quality of learning in higher education, particularly in preparing PGSD students as independent, creative, and prepared elementary school teacher candidates to face the challenges of 21st-century education.